Evaluation of cases of spontaneous conceptions during COVID-19 outbreak and lock down: multicentric retrospective analytic study - Patil, Deepak (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: With lockdown and cessation of non essential, life saving treatment options couples registered at ART centres were dismayed. The aspirations of numerous couples and their families were left in a lurch. Unexpectedly cases of spontaneous conceptions in this pool of patients were a ray of hope. Methods: In this multicentric retrospective analytic study, we evaluated all cases of spontaneous pregnancies and compared them with the cohort of couples registered at our ART centers. The objective of the study was to study impact of pandemic on ART registered couples. Results: Comparisons showed that the patients who had conceived were younger with a shorter duration of infertility. More of unexplained infertile patients conceived as compared to those with known etiology. Genital tuberculosis remained constant subset of patient who conceived spontaneously as before. Conclusions: Age and duration of infertility remains important prognostic indicator for spontaneous conception in Infertile couples. The pandemic had positive impact on conception rate in our clientele.